Static analysis : 23rd International Symposium, SAS 2016, Edinburgh, UK, September 8-10, 2016, proceedings /: 23rd International Symposium, SAS 2016, Edinburgh, UK, September 8-10, 2016, proceedings. (2016) - Unknown
No abstract available